New faunistic and taxonomic insights on little known Crambidae from forested habitats of Italian Peninsula (Lepidoptera: Pyraloidea) - S. Scalercio; A. Ienco; S. Greco (SHILAP)
We provided new distribution data and taxonomic notes concerning eleven Crambidae species new or little known for the Italian fauna. Most records were collected in Calabria, the southernmost region of peninsular Italy, where forested habitats were surveyed during last years. Some accessory data were mined from Barcode of Life Data System (BOLD) and were used to refine the distribution of treated species. In detail, we found three species new for Italian fauna: Evergestis subfuscalis (Staudinger, 1870), Udea languidalis (Eversmann, 1842), and Hyperlais siccalis (Guenée, 1854). Three species not recorded in peninsular Italy so far: Cynaeda gigantea (Wocke, 1871), Evergestis dumerlei Leraut, 2003, and Catoptria staudingeri (Zeller, 1863). Four species not recorded in southern Italy so far, Evergestis infirmalis (Staudinger, 1870), Cynaeda dentalis ([Denis & Schiffermüller], 1775), Paratalanta pandalis (Hübner, 1796), Hodebertia testalis (Fabricius, 1794). Evergestis sophialis (Fabricius, 1787) was for the first time recorded in Calabria. Barcoding analysis allowed us to confirm the status of Evergestis subfuscalis as bona species, eastern vicariant of E. mundalis. Furthermore, we underlined the needs of a revision of the Udea fimbriatralis species group as barcodes of western and eastern European specimens appear to be intermingled, suggesting the presence of one unique variable species. In conclusion, the importance of the Italian peninsula as a bridge between western and eastern European faunas was remarked.